PENGARUH KOMPONEN PENGENDALIAN INTERN TERHADAP KEPUTUSAN PEMBERIANKREDIT PADA BANK PERKREDITAN RAKYAT DI KABUPATEN TABANAN - Danayasa, I Gede Suka; Suardikha, I Made Sadha (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
Normal 0 false false false IN X-NONE X-NONE This study aims to determine the effect of the internal control components on the BPR in an effort to decide the provision of credit. The samples in this study using proportionate stratified random sampling method, the number of observations of 8 samples. The technique of collecting data using questionnaires and survey respondents as many as 32 respondents. The data analysis technique used is Moderated Regression Analysis (MRA). Based on the results of linear regression analysis found that (1) an assessment of the risk of an effect on lending decisions; (2) Information and communication have no effect on lending decisions; (3) control activities affect lending decisions; (4) monitoring the effect on lending decisions and; (5) the control environment influence on lending decisions on BPR in Tabanan.
Keywords: Internal Control Components, Decision Lending, Rural Banks